Mechanism study and characterization of crystalline nano-cellulose (cnc) from sawdust - Tang, Shin Yee (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This project was proposed to investigate the structure mechanism and characterization of crystalline nanocellulose (CNC) by dissolution of sawdust. Sawdust has been used as raw material to generate CNC. Furniture industry requires huge volume supply of wood to make furniture hence there was a huge amount of sawdust will be produced in grinding process. Sawdust used to produce CNC will be added value for sawdust. CNC was produced by alkaline pretreatment and acid hydrolysis. HCl was used in the experiment with addition of water (H2O) to produce CNC. The main purpose of acid hydrolysis and alkaline pretreatment was to remove lignin and hemicellulose. Centrifugation process repeat for three times for better separation of CNC from sawdust. The CNC produced is in solid form and black in color. The hydrolysis mechanism of cellulose with HCl was proved by program Gaussian 09. The process of hydrolysis mechanism is occurred during acid hydrolysis in present of water molecule. Moreover, characterization of CNC is done by using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM) test. From the relevance of FTIR peak, the lignin and hemicellulose was successfully remove from sawdust and generate CNC.